Análise comparativa de preços: estudo de variáveis influentes na percepção de vantagem de compra - Santos, Jorge Henrique França dos (2006)
This thesis treats some variables that can influence the consumer’s perception in the context of price’s comparative analysis in a purchase process. These variables were: the products’s offer presentation, study’s respondents scholarship and the product’s familiarity of the respondents. This study’s importance is grounded in the needs of perception’s understanding of a advantage in a product buying process in face of these study’s variables influencies, with the purpose to put in practice the results in the retail market. The research was developed as an empirical study, at São Luís City(MA), using a sample of one hundred and ninety two respondents equally divided between students of median and high scholarship degree. The study’s respondents evaluated purchase situations in a fictitious cenarios with different products presentation’ offers, where advantage’s perception was evaluated in terms of the scholarships and familiarities used in the study. The theoretical background to the work development considered Prospect’s Theory from Kahneman and Tversky (1979) and Mental Accounting Theory of Thaler (1985). Due to the nature of the database, was used non-parametric statistical tests of Friedman,Kruskal-Wallis, Wilcoxon and Mann-Wihtney. The final results confirm the hypothesis raised, and generated background for future research involving the variable of familiarity related to product’s brands.